IMPLEMENTATION OF PROFESSIONAL SELF-EDUCATION OF TEACHERS OF SCIENTIFIC LYCEUMS USING CLOUD-ORIENTED SERVICES OF OPEN SCIENCE - Kovalenko, Valentyna (Physical and Mathematical Education, 2023)
The article examines the peculiarities of the implementation of professional self-education of teachers of scientific lyceums using cloud-oriented services of open science. Scientific publications with various methods of using cloud services in training and improving the qualifications of specialists, particularly teachers, were analyzed. The key stages of the implementation of professional self-education of teachers of scientific lyceums have been determined. The ways of using cloud-oriented services of open science for self-education of teachers are described, namely: storage and exchange of materials; personalization of training; online courses and educational platforms; cooperation and exchange of experience; web tools for creating educational resources; evaluation and feedback.Formulation of the problem. For this study, it is important to analyze the features of the implementation of professional self-education of teachers of scientific lyceums using cloud-oriented services of open science. Materials and methods. A complex of methods was used, namely: analysis, systematization, generalization of scientific sources, analysis of scientific publications of domestic and foreign scientists, the method of going from the abstract to the concrete, conversations with teachers of scientific lyceums, generalization of own experience, etc. The results. The study analyzed the peculiarities of the implementation of professional self-education of teachers of scientific lyceums using cloud-oriented services of open science. The key stages of the implementation of professional self-education of teachers of scientific lyceums have been determined. The ways of using cloud-oriented services of open science for self-education of teachers are described, namely: storage and exchange of materials; personalization of training; online courses and educational platforms; cooperation and exchange of experience; web tools for creating educational resources; evaluation and feedback. Recommendations for teachers of scientific lyceums on ways to use cloud-oriented services of open science have been formed. Conclusions. The use of cloud-oriented services of open science for self-education of teachers allows to improve the learning process and make it more effective, interesting and accessible. At the same time, such a teacher's professional growth directly affects the quality of his students' education. The main advantages of using cloud-based services in the professional self-education of teachers are: 1) a large selection of resources; 2) flexibility and availability; 3) constant updating of information/data; 4) interaction and cooperation.
Keywords: professional development; self-education; open science; cloud-oriented services; teachers